Designing SOP for Quality Document Control in Rumah BUMN Bandung using Business Process Management Method - Faisal Fathurrahman; Sri Widaningrum; Wiyono Sutari (School of Industrial and System Engineering, Telkom University, 2024)
The role of Micro, Small and Medium Enterprises (MSMEs) is very important for a region, especially asone of the drivers of economic growth in the region. In order to create efficiency, wider market reach,attract more customers and better business opportunities, MSMEs must enter the digital businessecosystem. Rumah BUMN (RB) is an initiative program of BUMN and the Ministry of BUMN tostrengthen Micro, Small and Medium Enterprises (MSMEs). Rumah BUMN Bandung is one of the activeRumah BUMN and there are many activities under the auspices of Bank BRI. As the digital businessecosystem develops, more and more MSMEs are joining Rumah BUMN Bandung. Implementation ofdocumentation at Rumah BUMN Bandung only reached 12.5%, mainly focused on training programs outof a total of 8 existing programs. The reason is that there is no comprehensive implementation of qualitydocument control standards at Rumah BUMN Bandung. As a result, Rumah BUMN Bandung employeesoften have difficulty finding documents, sometimes documents that have expired are still being used, andthey make mistakes in providing documents to fellow employees. This research aims to describedocuments that need to be controlled, design SOPs for quality document control, and create use casediagrams. The method used in this research is Business Process Management (BPM). In an effort to dealwith existing problems, SOPs and use case diagrams of the quality document control process will bedesigned.